Finding ‘My Happy Place’: Promoting Cooperative Behavior through Place Attachment and Place Memory - Manitar, Erlis; Pelupessy, Dicky Chresthover (Jurnal Pendidikan Indonesia, 2025)
This narrative literature review article aims to understand how cooperative behavior in society can be driven by place attachment and place memory. This review integrates international and local findings. Studies in Indonesia, such as Jakarta, Bandung, and Pekalongan, show that emotional experiences, social interactions, and the physical characteristics of public spaces collectively shape place attachment, which ultimately strengthens cooperative behavior. This study contributes to the understanding of place attachment and place memory and recommends the importance of public space design that can support emotional and social engagement within communities.